The Synergy of Financial Innovation, Corporate Social Responsibility, and HRM Morale: A Systematic Review on Their Impact on Firm Image and Business Interest - Yusuf, Marwah; Putra, Aditya Halim Perdana Kusuma (Jurnal Manajemen Bisnis, 2024)
This study aims to explore the synergy between financial innovation, Corporate Social Responsibility (CSR), and Human Resource Management (HRM) morale, focusing on their collective impact on firm image and business interest. Utilizing a qualitative approach through a systematic literature review, this research synthesizes findings from recent empirical studies to provide a comprehensive understanding of how these elements interact to create a sustainable competitive advantage. The systematic review follows the PRISMA guidelines to ensure rigor and transparency in identifying, selecting, and analyzing relevant literature. The results of the study indicate that financial innovation, particularly through fintech and blockchain technologies, enhances operational efficiency and aligns with broader societal goals through sustainable finance practices. CSR is shown to significantly improve firm image by fostering trust and loyalty among stakeholders, while HRM morale is identified as a critical factor in enhancing organizational resilience, especially during crises such as the COVID-19 pandemic. The most significant finding is the synergistic relationship between financial innovation, CSR, and HRM morale, which collectively contribute to a sustainable competitive advantage that enhances firm performance and stakeholder engagement. The study concludes that integrating these elements into a cohesive strategy is essential for firms seeking long-term success in the modern business environment. The implications are significant for both theory and practice, offering a novel framework for future research and practical guidance for managers.